Aqueous zinc ion battery electrolyte and aqueous zinc ion battery

CN118017032BActive Publication Date: 2026-10-30QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410188991.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-20
Publication Date
2026-10-30
Estimated Expiration
2044-02-20

AI Technical Summary

Technical Problem

在位于双电层中的锌离子电镀的去溶剂化过程中,需要克服能量势垒,会释放大量不稳定的游离活性水分子,这种水分子具有减弱的H-O键,更容易分解产生氢,导致金属Zn附近局部微环境的pH增加,会致使锌负极发生腐蚀钝化等副反应,并进一步导致锌枝晶的生长

Benefits of technology

[0011]1.本发明向水系锌离子电池电解液中添加的添加剂包括异丙醇和氟硼酸根,异丙醇会参与锌离子溶剂化结构中,并通过与氟硼酸根的双效协同作用使氟硼酸根也进入锌离子溶剂化结构中,减少锌离子去溶剂化过程中活性水的产生,抑制了水的活性,实现了宽的电化学稳定窗口,抑制了水系锌离子电池负极的副反应以及枝晶生长,稳定了电极/电解质界面。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118017032B_ABST
    Figure CN118017032B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of aqueous zinc ion batteries, and relates to an aqueous zinc ion battery electrolyte and an aqueous zinc ion battery. Water is used as a solvent, a zinc salt is used as an electrolyte, and isopropyl alcohol and a fluoroborate are used as additives. The volume concentration of isopropyl alcohol in the electrolyte is 0.1-10%, and the concentration of sodium fluoroborate in the electrolyte is 0.01-0.5 mol / L. By regulating the solvation structure of zinc ions, the application reduces active water molecules generated in the electroplating process, regulates the electrode / electrolyte interface, reduces the direct contact between the zinc negative electrode and H2O molecules, thereby inhibiting the side reactions such as hydrogen evolution, corrosion and passivation of the zinc negative electrode, and achieving the effect of optimizing the electrode / electrolyte interface. Meanwhile, the gradient interface phase formed on the surface of the Zn metal inhibits the serious dendrite problem caused by the non-uniform deposition of the negative electrode zinc ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of aqueous zinc-ion batteries, and relates to an aqueous zinc-ion battery electrolyte and an aqueous zinc-ion battery. Background Technology

[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

[0003] Aqueous zinc-ion batteries (ZIBs) are considered a promising alternative to rechargeable lithium-ion batteries (LIBs) due to their large capacity, abundant resources, and compatibility of zinc with safe and stable aqueous electrolytes. They possess high theoretical capacities (820 mAh / g, 5854 mAh / cm³). 2 Zinc oxide (ZIB) boasts advantages such as low redox potential, non-toxicity, abundant reserves, reasonable price, and environmental friendliness. However, the growth of zinc dendrites and side reactions in the negative electrode still hinder the development of ZIB. However, due to the presence of Zn... 2+ The reduction potential of Zn is lower than that of the hydrogen evolution reaction, which leads to instability in the electroplating and stripping process of zinc metal in water, resulting in serious side reactions and corrosion / passivation of the zinc anode. The reasons can be summarized as follows: In aqueous electrolytes, water molecules will encapsulate zinc ions, forming solvent ionic groups with oriented and ordered structures—[Zn-(H2O). n ] 2+ During the desolvation process of zinc ion electroplating located in the double layer, an energy barrier needs to be overcome, which releases a large number of unstable free active water molecules. These water molecules have weakened H2O bonds and are more likely to decompose to produce hydrogen, leading to an increase in the pH of the local microenvironment near the metal Zn. This causes side reactions such as corrosion and passivation of the zinc anode, and further leads to the growth of zinc dendrites. Summary of the Invention

[0004] To address the shortcomings of existing technologies, the present invention aims to provide an aqueous zinc-ion battery electrolyte and an aqueous zinc-ion battery. This invention reduces the amount of active water molecules generated during the electroplating process by regulating the solvation structure of zinc ions and by controlling the electrode / electrolyte interface to reduce direct contact between the zinc anode and H₂O molecules. This suppresses side reactions such as hydrogen evolution, corrosion, and passivation of the zinc anode, thereby optimizing the electrode / electrolyte interface. Simultaneously, it suppresses severe dendrite formation caused by uneven deposition of zinc ions on the Zn metal surface by forming a gradient interface phase.

[0005] To achieve the above objectives, the technical solution of the present invention is as follows:

[0006] On one hand, an aqueous zinc-ion battery electrolyte uses water as a solvent, zinc salt as an electrolyte, and isopropanol and fluoroborate as additives. The volume concentration of isopropanol in the electrolyte is 0.1-10%, and the concentration of fluoroborate in the electrolyte is 0.01-0.5 mol / L. The cation of the fluoroborate is ammonium ion or a metal cation other than zinc ion.

[0007] This invention adds isopropanol and fluoroborate as additives to an aqueous zinc-ion battery electrolyte. Isopropanol can replace water molecules in the Zn electrolyte. 2+ The external solvation shell structure, and its synergistic effect with fluoroborate, promotes the substitution of water molecules by fluoroborate ions for water molecules in Zn. 2+ In the solvation sheath, a gradient bilayer SEI layer rich in ZnF2 and Zn3B2O6 is induced to form on the negative electrode. By utilizing the synergistic effect of the above-mentioned fluoroborate and isopropanol, the stability of the negative electrode of the aqueous zinc-ion battery can be effectively improved.

[0008] This invention adds isopropanol and sodium fluoroborate as additives to the electrolyte of aqueous zinc-ion batteries, enabling comprehensive manipulation of H2O molecules while simultaneously achieving hydrogen bond reconstruction, solvation shell optimization, and a multifunctional bilayer Zn-electrolyte interface. This electrolyte strategy exhibits excellent environmental adaptability, suppresses water activity, achieves a wide electrochemical stability window, inhibits side reactions and dendrite growth at the anode of aqueous zinc-ion batteries, stabilizes the electrode / electrolyte interface, and achieves high zinc plating / stripping efficiency.

[0009] On the other hand, an aqueous zinc-ion battery includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the electrolyte is the aqueous zinc-ion battery electrolyte described above.

[0010] The beneficial effects of this invention are as follows:

[0011] 1. The additives added to the aqueous zinc-ion battery electrolyte of this invention include isopropanol and fluoroborate. Isopropanol participates in the zinc ion solvation structure and, through the synergistic effect with fluoroborate, allows fluoroborate to also enter the zinc ion solvation structure, reducing the generation of active water during zinc ion desolvation, inhibiting water activity, achieving a wide electrochemical stability window, suppressing side reactions and dendrite growth at the negative electrode of the aqueous zinc-ion battery, and stabilizing the electrode / electrolyte interface.

[0012] 2. In the aqueous zinc-ion battery provided by this invention, fluoroborate groups in the electrolyte react with zinc metal atoms on the zinc negative electrode surface, sequentially generating Zn3B2O6 and ZnF2 on the Zn metal surface, forming a gradient ZnF2-Zn3B2O6 interface phase. The outer ZnF2 layer can promote the growth of Zn... 2+ Desolvation, internal Zn3B2O6 can act as a rapid Zn...2+ The transport channels promote the uniform deposition of zinc ions at the negative electrode. The synergistic effect of these two factors suppresses the growth of zinc dendrites and the occurrence of side reactions at the negative electrode, resulting in good cycle stability in aqueous zinc-ion batteries using fluoroborate as an additive.

[0013] 3. The preparation process of the aqueous zinc-ion battery electrolyte provided by this invention is simple and feasible. It only requires adding a small amount of isopropanol as a diluent to the electrolyte according to the required concentration, and adding a small amount of fluoroborate as an additive to the electrolyte according to the required concentration, followed by battery assembly. Furthermore, the raw materials used in this invention are environmentally friendly and inexpensive. Attached Figure Description

[0014] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0015] Figure 1 This is a comparison chart of the cycle life of zinc symmetric batteries in Example 1 and Comparative Example 1 of the present invention;

[0016] Figure 2 These are XRD comparison images of the zinc symmetric cells of Example 1 and Comparative Example 1 of the present invention.

[0017] Figure 3 SEM images of zinc foil after constant current charge and discharge of the zinc symmetric battery of Example 1 and Comparative Example 1 of the present invention, a is the experimental sample and b is the control sample;

[0018] Figure 4 This is a comparison chart of the cycle life of zinc-copper asymmetric batteries assembled in Example 2 and Comparative Example 2 of the present invention;

[0019] Figure 5 This is a comparison chart of the cycle performance of aqueous zinc-ion full batteries assembled in Example 3 and Comparative Example 3 of the present invention. Detailed Implementation

[0020] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0021] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0022] Given that aqueous zinc-ion batteries suffer from problems such as unstable zinc plating and stripping processes in water, leading to severe side reactions, as well as corrosion / passivation of the zinc anode, this invention proposes an aqueous zinc-ion battery electrolyte and an aqueous zinc-ion battery.

[0023] In a typical embodiment of the present invention, an aqueous zinc-ion battery electrolyte is provided, using water as a solvent, zinc salt as an electrolyte, and isopropanol and fluoroborate as additives. The volume concentration of isopropanol in the electrolyte is 0.1-10%, and the concentration of sodium fluoroborate in the electrolyte is 0.01-0.5 mol / L. The cation of the fluoroborate is ammonium ion or a metal cation other than zinc ion.

[0024] The fluoroborates described in this invention include, for example, sodium fluoroborate, potassium fluoroborate, and ammonium fluoroborate. In the embodiments of this invention, sodium fluoroborate was used as an additive for verification, and the effect was excellent. However, excessively high concentrations of fluoroborates added in this invention can cause severe corrosion to the zinc anode, thereby affecting the lifespan of the zinc-ion battery. Adding zinc fluoroborate as an additive will alter the zinc ion concentration, thus affecting the performance of the zinc-ion battery.

[0025] In some embodiments, the concentration of fluoroborate in the electrolyte is 0.1 to 0.5 mol / L.

[0026] In some embodiments, the concentration of fluoroborate in the electrolyte is 0.2 to 0.4 mol / L.

[0027] In some embodiments, the volume concentration of isopropanol in the electrolyte is 1 to 10%.

[0028] The zinc salt described in this invention is a compound whose cation is zinc ion. In some embodiments, the zinc salt is selected from one or more of zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc perchlorate, zinc tetrafluoroborate, and zinc trifluoromethanesulfonate. The concentration of the zinc salt in the electrolyte is 1 to 3 mol / L.

[0029] Another embodiment of the present invention provides an aqueous zinc-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the electrolyte is the aqueous zinc-ion battery electrolyte described above.

[0030] The negative electrode material described in this invention is metallic zinc, and the negative electrode can be one of zinc sheet, zinc foil, and zinc alloy.

[0031] In some embodiments, the positive electrode includes a current collector, an active material, a binder, and a conductive agent. The binder is, for example, polyvinylidene fluoride (PVDF). The conductive agent is, for example, the conductive agent Super P.

[0032] In one or more embodiments, the positive electrode is prepared by: adding active material, binder and conductive agent to solvent and mixing evenly to obtain slurry, coating the slurry onto current collector and drying it.

[0033] The active material in the positive electrode of this invention is a zinc ion intercalating material or an organic redox active material, such as zinc oxide, zinc vanadium oxide, zinc manganate, etc. In one or more embodiments, the active material in the positive electrode is PEDOT-intercalated vanadium pentoxide. Specifically, the preparation method of PEDOT-intercalated vanadium pentoxide is as follows: EDOT (3,4-ethylenedioxythiophene) is added to a vanadium pentoxide solution, and the mixture is heated under reflux to react, thus obtaining the material.

[0034] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments and comparative examples.

[0035] Example 1

[0036] (1) Preparation of negative electrode sheet. Cut zinc foil into electrode sheets with a diameter of 12 mm, press them under a pressure of 5 MPa for 5 min, then polish the zinc sheet with 2000-grit sandpaper, place it in an ethanol solution, sonicate for 5 min, and air dry naturally to obtain zinc electrode sheet.

[0037] (2) Prepare the electrolyte. Based on 2 mol / L ZnSO4, add sodium fluoroborate as an electrolyte additive with a concentration of 0.5 mol / L, and add 10% isopropanol by volume. Stir for 30 min.

[0038] (3) Assemble a symmetrical battery according to the following components: negative electrode shell, negative electrode pad, negative electrode, separator, electrolyte, negative electrode, negative electrode pad, and negative electrode shell.

[0039] Comparative Example 1

[0040] (1) Preparation of negative electrode sheet. Cut zinc foil into electrode sheets with a diameter of 12 mm, press them under a pressure of 5 MPa for 5 min, then polish the zinc sheet with 2000-grit sandpaper, place it in an ethanol solution, sonicate for 5 min, and air dry naturally to obtain zinc electrode sheet.

[0041] (2) Prepare an electrolyte of 2 mol / L ZnSO4.

[0042] (3) Assemble a symmetrical battery according to the following components: negative electrode shell, negative electrode pad, negative electrode, separator, electrolyte, negative electrode, negative electrode pad, and negative electrode shell.

[0043] Test plan and analysis results

[0044] The symmetrical batteries assembled in Example 1 and Comparative Example 1 operate at 1.0 mA.cm -2After looping, Figure 1 The experimental sample was a symmetrical cell from Example 1 at 1.0 mA.cm -2 The discharge cycle performance graph shows that stable cycling reached 3000 cycles. The control sample is a symmetrical battery (Comparative Example 1) at 1.0 mA.cm⁻¹. -2 The discharge cycle performance diagram shows that the stable cycle only reached 500 cycles. Figure 2 The XRD pattern of the products on the negative electrode surface is shown. In Comparative Example 1 (control sample), the diffraction intensity of the Zn(002) plane diffraction peak is high, making it easier to form dendrites. Compared with Comparative Example 1, no basic zinc sulfate byproduct was formed in Example 1 (experimental sample). Figure 3 The experimental and control samples are SEM images of the surfaces of symmetrical cells assembled in Example 1 and Comparative Example 1 after 1000 cycles, respectively. Comparative Example 1 shows dendrite formation and unevenness on its surface. In contrast, Example 1 shows no severe dendrite formation on its surface.

[0045] Example 2

[0046] (1) Preparation of negative electrode sheet. Cut zinc foil into electrode sheets with a diameter of 12 mm, press them under a pressure of 5 MPa for 5 min, then polish the zinc sheet with 2000-grit sandpaper, place it in an ethanol solution, sonicate for 5 min, and air dry naturally to obtain zinc electrode sheet.

[0047] (2) Preparation of positive electrode sheet. Cut copper foil into electrode sheets with a diameter of 12 mm, press them under a pressure of 5 MPa for 5 min, then place them in an ethanol solution, sonicate for 5 min, and air dry them naturally to obtain copper electrode sheets.

[0048] (3) Prepare the electrolyte. Based on 2 mol / L ZnSO4, add sodium fluoroborate as an electrolyte additive with a concentration of 0.5 mol / L, and add 10% isopropanol by volume. Stir for 30 min.

[0049] (4) Assemble a zinc-copper asymmetric battery according to the following components: negative electrode shell, negative electrode pad, negative electrode, separator, electrolyte, positive electrode, positive electrode pad, and positive electrode shell.

[0050] Comparative Example 2

[0051] (1) Preparation of negative electrode sheet. Cut zinc foil into electrode sheets with a diameter of 12 mm, press them under a pressure of 5 MPa for 5 min, then polish the zinc sheet with 2000-grit sandpaper, place it in an ethanol solution, sonicate for 5 min, and air dry naturally to obtain zinc electrode sheet.

[0052] (2) Preparation of positive electrode sheet. Cut copper foil into electrode sheets with a diameter of 12 mm, press them under a pressure of 5 MPa for 5 min, then place them in an ethanol solution, sonicate for 5 min, and air dry them naturally to obtain copper electrode sheets.

[0053] (3) Prepare an electrolyte of 2 mol / L ZnSO4.

[0054] (4) Assemble a zinc-copper asymmetric battery according to the following components: negative electrode shell, negative electrode pad, negative electrode, separator, electrolyte, positive electrode, positive electrode pad, and positive electrode shell.

[0055] Comparison of test plans and results

[0056] The zinc-copper asymmetric batteries assembled in Example 2 and Comparative Example 2 operate at 1.0 mA.cm -2 After looping, Figure 4 The experimental sample was the zinc-copper asymmetric cell from Example 2 at 1.0 mA / cm². -2 The discharge cycle performance graph shows a stable cycle time of 1200 cycles. The control sample is the zinc-copper asymmetric battery (Comparative Example 2) at 1.0 mA / cm². -2 The discharge cycle performance diagram shows that the stable cycle only reached 100 cycles.

[0057] Example 3

[0058] (1) Preparation of the positive electrode sheet. 1.455 g of V2O5 was dissolved in 300 mL of ultrapure water, and then 0.682 g of EDOT was added with stirring. The yellow solution was then transferred to a three-necked flask and refluxed at 100 °C for 12 hours. The dark green precipitate was collected by filtration and washed several times with deionized water and ethanol. Finally, the sample was obtained by drying in a vacuum oven at 60 °C for 12 hours. After grinding, the obtained powder, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were mixed evenly in a ratio of 7:2:1. N-methyl-2-pyrrolidone (NMP) was added and mixed evenly. The mixture was then rolled on a stainless steel mesh and dried in an oven at 60 °C for 24 hours. The dried sample was then ready for use.

[0059] (2) Preparation of negative electrode sheet. Cut zinc foil into electrode sheets with a diameter of 12 mm, press them under a pressure of 5 MPa for 5 min, then polish the zinc sheet with 2000-grit sandpaper, place it in an ethanol solution, sonicate for 5 min, and air dry naturally to obtain zinc electrode sheet.

[0060] (3) Prepare the electrolyte. Based on 2 mol / L ZnSO4, add sodium fluoroborate as an electrolyte additive with a concentration of 0.05 mol / L, and add 10% isopropanol by volume. Stir for 30 min.

[0061] (4) Assemble the battery in the following order: positive electrode shell, positive electrode plate, separator, electrolyte, negative electrode plate, gasket, spring sheet, and negative electrode shell. Compact the battery with a tablet press.

[0062] Comparative Example 3

[0063] (1) Preparation of the positive electrode sheet. 1.455 g of V2O5 was dissolved in 150 mL of ultrapure water, and then 0.682 g of EDOT was added with stirring. The yellow solution was then transferred to a three-necked flask and refluxed at 100 °C for 12 hours. The dark green precipitate was collected by filtration and washed several times with deionized water and ethanol. Finally, the sample was obtained by drying in a vacuum oven at 60 °C for 12 hours. After grinding, the obtained powder, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) were mixed evenly in a ratio of 7:2:1. N-methyl-2-pyrrolidone (NMP) was added and mixed evenly. The mixture was then rolled on a stainless steel mesh and dried in an oven at 60 °C for 24 hours. The dried sample was then ready for use.

[0064] (2) Preparation of negative electrode sheet. Cut zinc foil into electrode sheets with a diameter of 12 mm, press them under a pressure of 5 MPa for 5 min, then polish the zinc sheet with 2000-grit sandpaper, place it in an ethanol solution, sonicate for 5 min, and air dry naturally to obtain zinc electrode sheet.

[0065] (3) Prepare an electrolyte of 2 mol / L ZnSO4.

[0066] (4) Assemble the battery in the following order: positive electrode shell, positive electrode plate, separator, electrolyte, negative electrode plate, gasket, spring sheet, and negative electrode shell. Compact the battery with a tablet press.

[0067] The test plan and analysis results after assembling the symmetrical battery in this embodiment are as follows: Figure 5 As shown.

[0068] Figure 5 The experimental sample was the PEDOT-V₂O₅||ZnSO₄ + isopropanol + sodium fluoroborate||Zn battery assembled in Example 1, with a current of 10 mA·g -1 Cyclic performance curves under current density discharge. The battery remained stable for 400 cycles, maintaining a capacity retention of 93.5% and a coulombic efficiency greater than 98%. The control sample was the PEDOT-V₂O₅||ZnSO₄||Zn battery assembled in Example 1, at 10 mA·g⁻¹. -1 Cyclic performance curves at current density discharge. After 400 cycles, the battery retains 81.4% of its capacity and has a coulombic efficiency greater than 98%.

[0069] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. An aqueous zinc-ion battery electrolyte, using water as a solvent and zinc salt as the electrolyte, characterized in that, Isopropanol and fluoroborate are used as additives. The volume concentration of isopropanol in the electrolyte is 0.1~10%, and the concentration of fluoroborate in the electrolyte is 0.01~0.5 mol / L. The cation of fluoroborate is ammonium ion or a metal cation other than zinc ion.

2. The aqueous zinc-ion battery electrolyte as described in claim 1, characterized in that, The concentration of fluoroborate in the electrolyte is 0.1~0.5 mol / L.

3. The aqueous zinc-ion battery electrolyte as described in claim 1, characterized in that, The concentration of fluoroborate in the electrolyte is 0.2~0.4 mol / L.

4. The aqueous zinc-ion battery electrolyte as described in claim 1, characterized in that, The volume concentration of isopropanol in the electrolyte is 1-10%.

5. The aqueous zinc-ion battery electrolyte as described in claim 1, characterized in that, The zinc salt is selected from one or more of zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc perchlorate, zinc tetrafluoroborate, and zinc trifluoromethanesulfonate; or, the concentration of the zinc salt in the electrolyte is 1 to 3 mol / L.

6. An aqueous zinc-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The electrolyte is the aqueous zinc-ion battery electrolyte according to any one of claims 1 to 5.

7. The aqueous zinc-ion battery as described in claim 6, characterized in that, The negative electrode is one of zinc sheets, zinc foil, and zinc alloys.

8. The aqueous zinc-ion battery as described in claim 6, characterized in that, The positive electrode includes a current collector, an active material, a binder, and a conductive agent.

9. The aqueous zinc-ion battery as described in claim 8, characterized in that, The positive electrode is prepared by adding active material, binder and conductive agent into solvent and mixing them evenly to obtain a slurry, coating the slurry onto the current collector and drying it.

10. The aqueous zinc-ion battery as described in claim 8, characterized in that, The active material in the positive electrode is PEDOT intercalated vanadium pentoxide.

Citation Information

Patent Citations

  • Aqueous zinc ion battery electrolyte and battery

    CN114388901A

  • Electrorite for zinc-air cell with excellent lifetime, cathode of zinc-air cell using the electrorite and zinc-air cell using the electrorite

    KR1020160009872A